The Performance Comparison of Multiloop PID Controller on NCS Temperature Plant Based on UDP and TCP - Feriyonika, Feriyonika; Hong, Tjan Swi; Fuadi, Miftah Hasan (Universitas Syiah Kuala, 2024)
Hardware implementations of networked control systems (NCS) are still rarely found in various research publications so that technical issues, such as how to measure random delay and substitute it into the control equation, still need to be studied further. This study is therefore aimed to compare the performance of NCS based on the used protocol in the ethernet network, i.e. user datagram protocol (UDP) or transmission control protocol (TCP), by applying it in room temperature plant. In this study, the controlled plant is influenced by the fan speed, heating, and window position plant. The heating plant is employed as the main control, while the others are set as sub-plants. The three plants use proportionalintegralderivative (PID) controller where they are regulated by fuzzy logic as the master control unit (MCU). The MCU and three PID controllers are located in the master terminal unit (MTU) while the actuators and sensors are located in the three different remote terminal units (RTU). The verification experiment shows that there is no overshoot on TCP-based NCS, while UDP has 0.725%. For the risetime, the response on UDP is faster than TCP (110.22 as compared to 138.18 s). The same thing also happened to the settling time, where the time with UDP was 101.86 s and 128.44 s for TCP.